(untitled) (Studia Prawnicze / The Legal Studies, 1981)
Criticizing Hegel’s views on state, Marks transformed Hegel’s conflict between individual and a state into a conflict between a private and public man. For Marks, state is an oppressor of an individual but — as a representative of a progressive class — it constitutes a progressive element of social development as well. However, while Hegel adores every state, Marks values only a progressive state. In spite of Marks’s criticism, a part of Hegel’s notions on state is true. Led by the idea which lay at the basis of all the theories of social contract, Hegel opposed the society of citizens and a state. Marks accepted the idea of necessary cooperation of people torn by conflicts as well, but he transformed Hegel’s con- tradition between society and a state into contradiction within the state itself. According to Marks a state constitutes a unity of contradictions in two senses: it unifies hostie classes which would otherwise ruin the society, and — what is more — at the same time it protects the ruling class and common interests of two antagonistic classes. Thus, serving the interests of the ruling class at the same time the state secures existence of the whole society and of its unity. The state created by the ruling class and serving its interests, alienates itself from this class and constitutes itself by choosing an élite of the ruling class, often contrary to the real will of the class as such. The state concentrates also the most capable forces of the oppressed class thus becoming a universal intelect. This double character is characteristic for a socialist state as well and it is strengthened when such state diverges from the working class because of buro- cratization. However, when classes disappear the state will disappear as well.